Three types of dislocation core structure in B2 alloys. (June 2016) - Paidar, Václav; Čák, Miroslav
Abstract: The mechanical properties are directly influenced by the properties of dislocation. In the relatively simple ordered structure of B2 type, the dislocation core structure is controlled by the stacking-fault-like defects as antiphase boundaries. It will be shown, that three types of B2 alloys can be distinguished differing by the degeneracy of antiphase-boundary-like defects energies on the {110} plane: crystallographic, two- and four-fold degenerated antiphase boundary energies. Various types of superlattice dislocation and their impact on dislocation mobility is discussed in this paper. Highlights: The stacking-fault-like defects in YAg are analysed. A mesoscopic model for dissociated total dislocations is developed. Various types of superlattice dislocation in different B2 alloys are classified. Dislocation behaviour controls ductility of B2 rare-earth alloys.